2010
DOI: 10.2106/jbjs.h.00497
|View full text |Cite
|
Sign up to set email alerts
|

Cognition Following Computer-Assisted Total Knee Arthroplasty

Abstract: Further research is needed to determine if fat and bone-marrow-debris embolization is truly decreased by the use of computer-assisted total knee arthroplasty and if such a reduction has any clinical relevance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…However, in a polytraumatized patient or a patient with pulmonary or cerebral injury from a trauma in addition to a long-bone fracture, decreasing emboli could be potentially life-saving. In addition, with the recent focus on changes in mini-mental status scores and cognitive impairment in patients after intramedullary canal manipulation, perhaps these clinical findings have always been evident and are only now being recognized [13][14][15][16][17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a polytraumatized patient or a patient with pulmonary or cerebral injury from a trauma in addition to a long-bone fracture, decreasing emboli could be potentially life-saving. In addition, with the recent focus on changes in mini-mental status scores and cognitive impairment in patients after intramedullary canal manipulation, perhaps these clinical findings have always been evident and are only now being recognized [13][14][15][16][17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
“…More recently, studies have examined cognitive deficits after orthopaedic procedures, mostly focusing on total joint arthroplasty and hip fracture surgery, with the rate of cognitive impairment noted to be as high as 73% [13][14][15][16][17] . Although many etiologies for these cognitive deficits have been discussed, to our knowledge, no one has yet directly demonstrated whether embolic events may be at least partially responsible.…”
mentioning
confidence: 99%
“…Cohorts in all these studies were, however, very small and offer low levels of evidence, and contradictory evidence does exist showing no difference in blood loss [25,33] and thromboembolic phenomena [13] between the two groups. More recently, in a prospective study examining cognitive change following TKA, Haytmanek et al [34] found no difference in postoperative cognitive function between navigated and conventional TKA cohorts. In a commentary on this methodologically well-designed study, Masri recommended that ''a larger sample size may be required to definitively prove that there is no such difference'' [35] (Haytmanek et al having only reviewed 61 patients in total).…”
Section: Mortality and Morbiditymentioning
confidence: 99%
“…However, a comparison study failed to show a decrease in postoperative confusion or respiratory thromboembolic events in patients undergoing navigated TKA vs conventional TKA. 29,30 Similarly, many studies reveal no difference in hemoglobin drop, blood loss, or transfusion requirements. 30 Although a reduction in outliers of mechanical axis may be achieved with the technique, other proposed outcomes have not been borne out in the research to date.…”
Section: Computer Navigationmentioning
confidence: 99%